Efektivitas Pelatihan Contextual Teaching and Learning (CTL) Guna Meningkatkan Kompetensi Pedagogik Guru Sekolah Dasar di Pulau Sebatik - Yusandi Rezki Fadhli; Nono Hery Yoenanto (Universitas Negeri Makassar, 2021)
Competency pedagogic is the ability to manage the learning of participants learners that includes an understanding of the participant students, The design and implementation of learning , evaluation of the results of learning, and the development of the participant students to actualize various potentials that its ( Mulyasa, 2009). This study aims to determine the effectiveness of Contextual Teaching and Learning training to improve the pedagogical competence of elementary school teachers on Sebatik Island. Mechanical collection of data in the form of tool measuring scale Likert, a matter of knowledge and observation guide. Design research that is used is pretest-posttest one group design with a number of subjects as much as 30 teachers of the school base . This study uses the analysis of the Wilcoxon signed rank test. The results of the analysis of the data shows the value of significance 0.000 <0.05 which means that there are differences in the mean scores of competence pedagogic between the results of the pretest participants of the training contextual teaching and learning with the results of the posttest participant training contextual teaching and learning.